2015
DOI: 10.1051/0004-6361/201526524
|View full text |Cite
|
Sign up to set email alerts
|

Orbital period decay of compact black hole X-ray binaries: the influence of circumbinary disks?

Abstract: Context. Recently, compact black hole X-ray binaries XTE J 1118+480 and A0620-00 have been reported to be experiencing a fast orbital period decay, which is two orders of magnitude higher than expected with gravitational wave radiation. Magnetic braking of an Ap/Bp star has been suggested to account for the period change when the surface magnetic field of the companion star B s > ∼ 10 4 G. However, our calculation indicates that anomalous magnetic braking cannot significantly contribute to the large orbital pe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…If the donor stars have a very strong magnetic field and a rel- atively high wind-driving efficiency, anomalously high orbitalperiod derivatives of black-hole LMXBs could be produced by anomalous magnetic braking (González Hernández et al 2017). In addition, circumbinary disks surrounding the binary may be an alternative mechanism as well (Chen & Li 2015;Chen & Podsiadlowski 2017 ).…”
Section: Discussion and Summarymentioning
confidence: 99%
“…If the donor stars have a very strong magnetic field and a rel- atively high wind-driving efficiency, anomalously high orbitalperiod derivatives of black-hole LMXBs could be produced by anomalous magnetic braking (González Hernández et al 2017). In addition, circumbinary disks surrounding the binary may be an alternative mechanism as well (Chen & Li 2015;Chen & Podsiadlowski 2017 ).…”
Section: Discussion and Summarymentioning
confidence: 99%
“…Recently, Chen & Li (2015) have proposed AML models including circumbinary discs as a possible way to explain the fast orbital period decays in these BHXBs. This work shows the evolution of orbital period and period derivative for XTE J1118+480 during ∼ 0.8 − 1.2 Gyr (for initial M2 ∼ 3 − 1.5 M⊙) of its binary evolution.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the detection of middleinfrared excesses from Spitzer (Muno & Mauerhan 2006) and WISE (Wang & Wang 2014) have been interpreted as evidence for the presence of candidate circumbinary discs, or Remillard (1986) jets (Gallo et al 2007), in these two BHXB systems. However, Chen & Li (2015) have presented AML models including circumbinary discs but found that both the required mass transfer rate and circumbinary disc mass are far greater than the values inferred from observations. This makes unlikely that circumbinary discs are the main cause of the rapid orbital decay observed in these two BHXBs.…”
Section: Introductionmentioning
confidence: 91%
“…Theoretically it is possible to explain the rapid orbital shrinkage of the BHLMXBs with reasonable values of M CB,0 and t vis,0 . It is known that a rapid orbital decay can accelerate mass loss from the donor, consequently enhance the X-ray luminosity (Justham et al 2006;Chen & Li 2015). However, observationally the three BHLMXBs are all faint sources.…”
Section: Cb Disk Fed By Single Outburstmentioning
confidence: 99%
“…In this subsection, we present the results in the pre-CB disk phase by calculating a number of evolutions with different initial values of M 2 and P orb . Several authors have theoretically investigated the properties of the donors in BHLMXBs (e.g., Podsiadlowski et al 2003;Ivanova 2006;Justham et al 2006;Yungelson & Lasota 2008;Chen & Li 2015;Fragos & McClintock 2015;Wang et al 2016). In Table 1, We list the observed parameters of the three BHLMXBs.…”
Section: Pre-cb Disk Evolutionmentioning
confidence: 99%